Li-Ion Cell Operation at Low Temperatures - Ji, Yan; Zhang, Yancheng; Wang, Chao-Yang (Journal of the Electrochemical Society, 2013)
Substantially reduced energy and power capabilities of lithium-ion cell operating at low temperatures pose a technical barrier for market penetration of hybrid electric vehicles and pure electric vehicles. The present work delineates Li-ion cell behaviors at low temperatures by a combined experimental and modeling approach. An electrochemical-thermal coupled model, incorporating concentration- and temperature-dependent transport and kinetic properties, is applied and validated against 2.2Ah 18650 cylindrical cells over a wide range of temperatures (−20°C to 45°C) and discharge rates. Simulation and experimental results demonstrate the dramatic effects of cell self-heating upon electrochemical performance. A nonisothermal Ragone plot accounting for these important thermal effects is proposed for the first time for Li-ion cells and more generally for thermally coupled batteries. Detailed resistance analysis indicates that performance limits at −20°C depend on not only discharge rates but also thermal conditions. Optimization of cell design parameters and material properties is performed for 1 C rate discharge starting from −20°C, where the principal performance limitations are found to be Li+ diffusion in the electrolyte and solid-state Li diffusion in graphite particles, instead of charge-transfer kinetic or ohmic resistance.